Cobalt-based amorphous composite plating solution, preparation method of cobalt-based amorphous composite plating solution, cobalt-based amorphous composite plating layer and preparation method and application of cobalt-based amorphous composite plating layer
Through the electroplating technology of cobalt-based amorphous composite plating solution, combined with the introduction of wear resistance and lubricating particles, the problem that existing composite plating layers are difficult to take into account both wear resistance and corrosion resistance, and the dual performance improvement of the plating is achieved.
Patent Information
- Application Number
- CN202510138766.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-05-09
AI Technical Summary
It is difficult for existing composite coatings to take into account both wear resistance and corrosion resistance, especially in high temperature, high pressure and strong friction conditions.
Cobalt-based amorphous composite plating solution is used to deposit the cobalt-based amorphous composite plating layer through electroplating technology, and wear-resistant particles and lubricating particles are introduced into the plating layer to improve the hardness and friction-reducing performance of the plating layer.
It achieves double improvement of the wear resistance and corrosion resistance of the coating, and can maintain excellent performance in a high-stress and high friction environment, extending the service life of mechanical parts.
Smart Images

Figure CN119956449A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrochemical deposition, and in particular to a cobalt-based amorphous composite plating solution and a preparation method thereof, a cobalt-based amorphous composite coating and a preparation method and application thereof. Background Art
[0002] With the rapid development of modern industry, mechanical parts operate under complex working conditions such as high temperature, high pressure and strong friction, which puts higher requirements on their surface performance, especially in terms of wear resistance and corrosion resistance. Although composite coating technology can improve the performance of coatings in some cases by co-depositing metal-based coatings with wear-resistant particles or lubricating particles, simple composite coatings often cannot take into account both wear resistance and corrosion resistance due to the complex and changeable environment. Summary of the invention
[0003] In view of this, the object of the present invention is to provide a cobalt-based amorphous composite plating solution and a preparation method thereof, a cobalt-based amorphous composite coating and a preparation method and application thereof. The cobalt-based amorphous composite plating solution of the present invention can make the prepared cobalt-based amorphous composite coating have both wear resistance and corrosion resistance.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The invention provides a cobalt-based amorphous composite plating solution, comprising the following components: 100-300 g / L of cobalt sulfate, 20-50 g / L of cobalt chloride, 20-50 g / L of sodium hypophosphite, 20-50 g / L of boric acid, 1-5 g / L of surfactant, 0.1-100 g / L of wear-resistant particles, and 0.1-100 g / L of lubricating particles.
[0006] Preferably, the wear-resistant particles include one or more of chromium carbide particles, cubic boron nitride particles, silicon carbide particles, tungsten carbide particles, aluminum oxide particles, titanium carbide particles, zirconium oxide particles and titanium boride particles.
[0007] Preferably, the lubricating particles include one or more of hexagonal boron nitride particles, graphite fluoride particles, molybdenum disulfide particles, graphite particles, polytetrafluoroethylene particles, aluminum nitride particles and boric acid particles.
[0008] The present invention also provides a method for preparing the cobalt-based amorphous composite plating solution described in the above technical solution, comprising the following steps:
[0009] Mixing wear-resistant particles, lubricating particles and a surfactant solution to obtain a mixed solution;
[0010] The mixed solution, cobalt sulfate, cobalt chloride, sodium hypophosphite and boric acid are mixed to obtain the cobalt-based amorphous composite plating solution.
[0011] The present invention also provides a method for preparing a cobalt-based amorphous composite coating, comprising the following steps:
[0012] Activating the workpiece to be plated in an activation solution to obtain an activated workpiece to be plated;
[0013] Using the activated workpiece to be plated as a cathode and a pure cobalt plate as an anode, electroplating is performed in a cobalt-based amorphous composite plating solution to obtain the cobalt-based amorphous composite coating;
[0014] The cobalt-based amorphous composite plating solution is the cobalt-based amorphous composite plating solution described in the above technical solution or the cobalt-based amorphous composite plating solution prepared by the preparation method described in the above technical solution.
[0015] Preferably, before the activation, the workpiece to be plated is degreased;
[0016] The degreasing liquid used in the degreasing comprises the following components: 30-50 g / L of sodium phosphate, 10-30 g / L of sodium silicate, 60-80 g / L of sodium hydroxide and 30-50 g / L of sodium carbonate;
[0017] The degreasing process is carried out at a temperature of 70 to 80° C. and for a time of 10 to 15 minutes.
[0018] Preferably, the activation solution comprises hydrochloric acid at a concentration of 50 to 250 g / L;
[0019] The activation time is 2 to 4 minutes.
[0020] Preferably, the electroplating is carried out under stirring conditions, and the stirring speed is 200 to 400 rpm;
[0021] The working temperature of the electroplating is 50-60°C, and the current density is 2-4A / dm 2 , time is 30 to 120 minutes; the distance between the anode and the cathode is 2 to 5 cm.
[0022] The present invention also provides a cobalt-based amorphous composite coating prepared by the preparation method described in the above technical solution.
[0023] The present invention also provides the use of the cobalt-based amorphous composite coating described in the above technical solution in wear-resistant and corrosion-resistant parts in aviation, aerospace or high-end mechanical equipment.
[0024] The present invention provides a cobalt-based amorphous composite plating solution, comprising the following components: 100-300 g / L of cobalt sulfate, 20-50 g / L of cobalt chloride, 20-50 g / L of sodium hypophosphite, 20-50 g / L of boric acid, 1-5 g / L of surfactant, 0.1-100 g / L of wear-resistant particles, and 0.1-100 g / L of lubricating particles. The cobalt-based amorphous composite coating prepared by the cobalt-based amorphous composite plating solution of the present invention can simultaneously meet the dual requirements of wear resistance and corrosion resistance. The present invention adopts a cobalt-based amorphous alloy as a metal matrix, and utilizes its non-static structure without grain boundaries to avoid the common dislocation slip phenomenon in traditional crystal structures, thereby improving the ability and hardness of the coating to resist plastic deformation. In addition, the reduced grain boundaries make the material surface smoother, and defects such as pores and cracks are significantly reduced, thereby reducing the probability of corrosion point formation, which can effectively prevent corrosion damage. On this basis, the cobalt-based amorphous alloy coating is compounded with wear-resistant particles and lubricating particles, wherein the wear-resistant particles are dispersed in the coating, play a role of pinning and strengthening, improve the hardness of the coating, and effectively transfer the load during the friction process, reduce the influence of external friction, and significantly improve the stability of the wear process; the lubricating particles form a lubricating film on the friction surface, reduce the friction coefficient, inhibit adhesive wear, and effectively control the damage of the wear debris to the coating, further improving the friction reduction performance of the coating. At the same time, the introduction of the wear-resistant particles and lubricating particles will also promote the refinement of the coating grains, make the coating more compact, further improve the hardness, and enhance the enrichment of phosphides on the coating surface; finally, the present invention, through the synergistic effect of wear-resistant particles and lubricating particles, makes the obtained composite coating not only show excellent wear resistance under high stress and high friction extreme working environment, but also have good self-lubricating performance, thereby significantly improving the overall performance of the composite coating, ensuring that mechanical parts have a longer service life and higher reliability under harsh conditions.
[0025] The present invention also provides a method for preparing a cobalt-based amorphous composite coating, comprising the following steps: activating a workpiece to be plated in an activation solution to obtain an activated workpiece to be plated; using the activated workpiece to be plated as a cathode and a pure cobalt plate as an anode, electroplating in a cobalt-based amorphous composite plating solution to obtain the cobalt-based amorphous composite coating; the cobalt-based amorphous composite plating solution is the cobalt-based amorphous composite plating solution described in the above technical solution or the cobalt-based amorphous composite plating solution prepared by the preparation method described in the above technical solution. The present invention adopts a cobalt-based amorphous alloy as a metal matrix, which not only provides excellent hardness and wear resistance, but also has excellent corrosion resistance, and can effectively slow down the damage of corrosion to the coating. In addition, the present invention adopts an electrodeposition method to make specific reinforcing particles (wear-resistant particles and lubricating particles) and cobalt-based amorphous alloy composite co-deposit, which can significantly improve the comprehensive performance of the coating, ensuring that mechanical parts have a longer service life and higher reliability under harsh conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 XRD graph (a) and potentiodynamic polarization curve (b) of the cobalt-based amorphous composite coating (cobalt-based amorphous-chromium carbide / graphite composite coating) described in Example 1 and the cobalt-based amorphous alloy coating described in Comparative Example 1 in a sodium chloride solution with a mass concentration of 3.5%;
[0027] Figure 2 The microscopic morphology of the cobalt-based amorphous composite coating described in Example 2 at different magnifications;
[0028] Figure 3 The wear resistance of the cobalt-based amorphous composite coating described in Example 3 was evaluated. DETAILED DESCRIPTION
[0029] The invention provides a cobalt-based amorphous composite plating solution, comprising the following components: 100-300 g / L of cobalt sulfate, 20-50 g / L of cobalt chloride, 20-50 g / L of sodium hypophosphite, 20-50 g / L of boric acid, 1-5 g / L of surfactant, 0.1-100 g / L of wear-resistant particles, and 0.1-100 g / L of lubricating particles.
[0030] In the present invention, unless otherwise specified, all preparation raw materials are commercially available products well known to those skilled in the art.
[0031] In the present invention, the cobalt-based amorphous composite plating solution comprises 100-300 g / L of cobalt sulfate, more preferably 150-250 g / L. In an embodiment of the present invention, the concentration of cobalt sulfate in the cobalt-based amorphous composite plating solution may be 200 g / L.
[0032] In the present invention, the cobalt sulfate provides cobalt ions.
[0033] In the present invention, the cobalt-based amorphous composite plating solution comprises 20-50 g / L of cobalt chloride, more preferably 30-40 g / L. In an embodiment of the present invention, the concentration of cobalt chloride in the cobalt-based amorphous composite plating solution may be 35 g / L.
[0034] In the present invention, the cobalt chloride provides part of the cobalt ions, while the chloride ions help to reduce anode passivation.
[0035] In the present invention, the cobalt-based amorphous composite plating solution includes 20-50 g / L sodium hypophosphite, more preferably 30-40 g / L. In an embodiment of the present invention, the concentration of sodium hypophosphite in the cobalt-based amorphous composite plating solution may be 35 g / L.
[0036] In the present invention, the sodium hypophosphite acts as a reducing agent to provide phosphorus atoms to promote co-deposition with cobalt ions.
[0037] In the present invention, the cobalt-based amorphous composite plating solution includes 20 to 50 g / L of boric acid, more preferably 30 to 40 g / L. In an embodiment of the present invention, the concentration of boric acid in the cobalt-based amorphous composite plating solution may be 35 g / L.
[0038] In the present invention, the role of the boric acid is to buffer and stabilize the pH value of the plating solution; at the same time, it can also be adsorbed on the electrode surface to improve the hydrogen evolution process.
[0039] In the present invention, the cobalt-based amorphous composite plating solution includes 1 to 5 g / L of a surfactant, more preferably 2 to 4 g / L. In an embodiment of the present invention, the concentration of the surfactant in the cobalt-based amorphous composite plating solution may be 2.5 g / L or 3 g / L.
[0040] In the present invention, the surfactant includes one or more of sodium dodecyl sulfate, sodium dodecylbenzene sulfonate, hexadecyltrimethylammonium bromide and polyethylene glycol. When the surfactant is two or more of the above specific selections, the present invention has no special restrictions on the ratio of the specific substances, and can be mixed in any ratio. In an embodiment of the present invention, the surfactant can be sodium dodecyl sulfate or polyethylene glycol and sodium dodecyl sulfate in a mass ratio of 1:1.
[0041] In the present invention, the role of the surfactant is to enhance the wetting effect of the plating solution, reduce the generation of bubbles, and improve the uniformity and density of the coating.
[0042] In the present invention, the cobalt-based amorphous composite plating solution comprises 0.1-100 g / L of wear-resistant particles, preferably 20-80 g / L. In an embodiment of the present invention, the concentration of wear-resistant particles in the cobalt-based amorphous composite plating solution may be 60 g / L.
[0043] In the present invention, the particle size of the wear-resistant particles is preferably 0.5 to 10 μm, more preferably 3 to 5 μm. The wear-resistant particles preferably include one or more of chromium carbide particles, cubic boron nitride particles (cBN particles), silicon carbide particles, tungsten carbide particles, aluminum oxide particles, titanium carbide particles, zirconium oxide particles and titanium boride particles. When the wear-resistant particles are two or more of the above-mentioned specific selections, the present invention does not have any special restrictions on the ratio of the above-mentioned specific substances, and they can be mixed in any ratio. In an embodiment of the present invention, the wear-resistant particles can be chromium carbide particles, silicon carbide particles or hBN particles.
[0044] In the present invention, chromium carbide particles have high hardness, high melting point and good oxidation resistance, are suitable for high temperature and heavy wear environment, and can effectively improve the wear resistance of the coating; cubic boron nitride particles are a superhard material second only to diamond, cubic boron nitride can greatly improve the hardness and wear resistance of the composite coating, and are suitable for high-speed cutting tools and high-load wear parts; silicon carbide particles are known for their high hardness, low density, chemical corrosion resistance and heat resistance, and silicon carbide particles can enhance the wear resistance of the coating, and are particularly suitable for high friction and low lubrication environments; tungsten carbide particles are widely used in composite coatings due to their extremely high hardness and wear resistance, and are used to improve The coating has excellent wear resistance, especially under high pressure and high friction working conditions. Alumina particles can effectively enhance the hardness and wear resistance of the coating, and have excellent chemical corrosion resistance, suitable for high temperature and high corrosion conditions. Titanium carbide particles have high hardness and good corrosion resistance. Titanium carbide can significantly improve the wear resistance of the composite coating and is suitable for long-term use in harsh environments. Titanium boride particles have extremely high hardness and excellent wear resistance. They are widely used in protective coatings and can effectively enhance the wear resistance of the coating. Zirconia particles have excellent thermal shock resistance and high temperature resistance. They are suitable for high temperature and high stress conditions and enhance the wear resistance and heat resistance of the coating.
[0045] In the present invention, the wear-resistant particles can improve the hardness and wear resistance of the composite coating.
[0046] In the present invention, the cobalt-based amorphous composite plating solution comprises 0.1-100 g / L of lubricating particles, preferably 20-80 g / L. In an embodiment of the present invention, the concentration of lubricating particles in the cobalt-based amorphous composite plating solution may be 30 g / L or 45 g / L.
[0047] In the present invention, the particle size of the lubricating particles is preferably 0.5 to 10 μm, more preferably 3 to 5 μm. The lubricating particles preferably include one or more of hexagonal boron nitride particles (hBN particles), graphite fluoride particles, molybdenum disulfide particles, graphite particles, polytetrafluoroethylene particles, aluminum nitride particles and boric acid particles. When the lubricating particles are two or more of the above specific selections, the present invention has no special restrictions on the ratio of the above specific substances, and they can be mixed in any ratio. In the present invention, hexagonal boron nitride particles provide excellent solid lubrication performance with a layered structure, and are suitable for friction parts in high temperature, vacuum and harsh environments; fluorinated graphite particles have excellent self-lubrication and high temperature resistance, can effectively reduce the friction coefficient of the coating, and are particularly suitable for high temperature and highly corrosive environments; molybdenum disulfide particles, due to their layered structure, show excellent friction reduction performance under high temperature and high load conditions, and are suitable for high temperature and high pressure environments; graphite particles are traditional solid lubricants, and graphite particles still maintain excellent lubrication effects under high temperature conditions, and are suitable for low speed and heavy load conditions; polytetrafluoroethylene (PTFE) particles have extremely low friction coefficients and excellent chemical stability, and are suitable for working environments with high self-lubrication requirements; aluminum nitride (AlN) particles have good thermal conductivity and lubricity, are suitable for high temperature friction conditions, and can effectively improve the heat dissipation and friction reduction effects of the composite coating; boric acid particles are widely used in lubrication occasions under high load and high pressure conditions due to their low friction coefficient and excellent friction reduction performance. In an embodiment of the present invention, the lubricating particles can be graphite particles, fluorinated graphite particles or hBN particles.
[0048] In the present invention, the lubricating particles can reduce the friction coefficient under high friction conditions and extend the service life of the workpiece.
[0049] In the present invention, the pH value of the cobalt-based amorphous composite plating solution is preferably 4.0-5.0, more preferably 4.5.
[0050] In the present invention, the solvent in the cobalt-based amorphous composite plating solution preferably includes deionized water.
[0051] The present invention also provides a method for preparing the cobalt-based amorphous composite plating solution described in the above technical solution, comprising the following steps:
[0052] Mixing wear-resistant particles, lubricating particles and a surfactant solution to obtain a mixed solution;
[0053] The mixed solution, cobalt sulfate, cobalt chloride, sodium hypophosphite and boric acid are mixed to obtain the cobalt-based amorphous composite plating solution.
[0054] The invention mixes wear-resistant particles, lubricating particles and a surfactant solution to obtain a mixed solution.
[0055] Before the mixing, the present invention also preferably includes washing, soaking, ultrasonicating and drying the wear-resistant particles and lubricating particles in sequence; the present invention does not have any special limitation on the washing, soaking, ultrasonicating and drying processes, and the processes well known to those skilled in the art can be used.
[0056] The present invention does not have any special limitation on the mixing process, and the mixing process may be carried out using a process well known to those skilled in the art.
[0057] After obtaining the mixed solution, the present invention mixes the mixed solution, cobalt sulfate, cobalt chloride, sodium hypophosphite and boric acid to obtain the cobalt-based amorphous composite plating solution.
[0058] The present invention does not have any special limitation on the mixing process, and the mixing process may be carried out using a process well known to those skilled in the art.
[0059] The present invention also provides a method for preparing a cobalt-based amorphous composite coating, comprising the following steps:
[0060] Activating the workpiece to be plated in an activation solution to obtain an activated workpiece to be plated;
[0061] Using the activated workpiece to be plated as a cathode and a pure cobalt plate as an anode, electroplating is performed in a cobalt-based amorphous composite plating solution to obtain the cobalt-based amorphous composite coating;
[0062] The cobalt-based amorphous composite plating solution is the cobalt-based amorphous composite plating solution described in the above technical solution or the cobalt-based amorphous composite plating solution prepared by the preparation method described in the above technical solution.
[0063] The present invention activates the workpiece to be plated in an activation liquid to obtain the activated workpiece to be plated.
[0064] The present invention does not have any special limitation on the type of the plated workpiece, and any type familiar to those skilled in the art can be used. In an embodiment of the present invention, the workpiece to be plated can be 30CrMnSiA high-strength steel.
[0065] Before performing the activation, the present invention preferably further comprises degreasing the workpiece to be plated.
[0066] In the present invention, the degreasing liquid used for degreasing preferably comprises the following components: 30-50 g / L sodium phosphate, 10-30 g / L sodium silicate, 60-80 g / L sodium hydroxide and 30-50 g / L sodium carbonate. In the present invention, the solvent of the degreasing liquid is preferably deionized water.
[0067] In the present invention, the degreasing liquid used for degreasing preferably includes 30 to 50 g / L of sodium phosphate, more preferably 35 to 45 g / L. In an embodiment of the present invention, the concentration of sodium phosphate in the degreasing liquid may be 40 g / L.
[0068] In the present invention, the role of the sodium phosphate is to effectively remove oil stains on the metal surface.
[0069] In the present invention, the degreasing liquid used for degreasing preferably includes 10 to 30 g / L of sodium silicate, more preferably 15 to 25 g / L. In an embodiment of the present invention, the concentration of sodium silicate in the degreasing liquid may be 30 g / L.
[0070] In the present invention, the role of the sodium silicate is to prevent grease and other impurities from gathering in the solution.
[0071] In the present invention, the degreasing liquid used for degreasing preferably includes 60 to 80 g / L of sodium hydroxide, more preferably 65 to 75 g / L. In an embodiment of the present invention, the concentration of sodium hydroxide in the degreasing liquid may be 70 g / L.
[0072] In the present invention, the role of the sodium hydroxide is to provide a highly alkaline environment to help dissolve the oily substances on the metal surface.
[0073] In the present invention, the degreasing liquid used for degreasing preferably includes 30 to 50 g / L of sodium carbonate, more preferably 35 to 45 g / L. In an embodiment of the present invention, the concentration of sodium carbonate in the degreasing liquid may be 40 g / L.
[0074] In the present invention, the role of the sodium carbonate is to effectively emulsify and dissolve oil stains.
[0075] In the present invention, the degreasing temperature is preferably 70-80° C., more preferably 73-76° C. The degreasing time is preferably 10-15 min, more preferably 15 min. In an embodiment of the present invention, the degreasing temperature may be 70° C., and the time may be 15 min.
[0076] In the present invention, the activation solution preferably includes a hydrochloric acid solution; the concentration of the hydrochloric acid is preferably 50 to 250 g / L, more preferably 250 g / L.
[0077] In the present invention, the activation time is preferably 2 to 4 minutes, more preferably 3 minutes; the temperature is preferably 20 to 30°C, more preferably 25°C.
[0078] After the activation is completed, the present invention also preferably includes washing with deionized water for 2 to 4 times, and more preferably includes washing with deionized water for 3 times.
[0079] The activated workpiece to be plated is obtained. The present invention uses the activated workpiece to be plated as a cathode and a pure cobalt plate as an anode to perform electroplating in a cobalt-based amorphous composite plating solution to obtain the cobalt-based amorphous composite coating.
[0080] Before performing the electroplating, the present invention also preferably includes installing an electroplating device. The installation of the electroplating device is preferably to place the activated workpiece to be plated and a pure cobalt plate with a clean surface in the cobalt-based amorphous composite plating solution, and the activated workpiece to be plated and the center of the cobalt plate are placed parallel to each other, with the activated workpiece to be plated as the cathode and the pure cobalt plate as the anode connected to an external constant current power supply.
[0081] In the present invention, the electroplating is preferably carried out under stirring conditions, and the stirring speed is preferably 200 to 400 rpm, more preferably 300 to 350 rpm. In an embodiment of the present invention, the stirring speed may be 325 rpm.
[0082] In the present invention, the working temperature of the electroplating is preferably 50-60°C, more preferably 53-56°C; the current density is preferably 2-4A / dm 2 , more preferably 3A / dm 2 The time is preferably 30 to 120 minutes, more preferably 60 minutes. The distance between the anode and the cathode is preferably 2 to 5 cm, more preferably 2.5 cm. In an embodiment of the present invention, the working temperature of the electroplating can be 55°C, and the current density can be 3A / dm 2 , the time can be 60 minutes, and the distance between the anode and the cathode can be 2.5 cm.
[0083] In the present invention, controlling the electroplating conditions within the above range can further ensure the quality of the prepared cobalt-based amorphous composite coating.
[0084] The present invention also provides a cobalt-based amorphous composite coating prepared by the preparation method described in the above technical solution.
[0085] The present invention also provides the application of the cobalt-based amorphous composite coating described in the above technical solution in wear-resistant and corrosion-resistant parts in aviation, aerospace or high-end mechanical equipment. The present invention does not have any special limitation on the method of the application, and the method well known to those skilled in the art can be used.
[0086] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0087] Example 1
[0088] The workpiece (made of 30CrMnSiA high-strength steel) was placed in a degreasing liquid (40 g / L sodium phosphate, 30 g / L sodium silicate, 70 g / L sodium hydroxide and 40 g / L sodium carbonate) for degreasing at 70°C for 15 min, and then washed with deionized water for 3 to 5 times to obtain a degreasing workpiece;
[0089] The degreased workpiece is placed in an activation solution (including a 250 g / L hydrochloric acid solution) for activation for 3 minutes, and then washed with deionized water for 2 to 3 times to obtain an activated workpiece to be plated;
[0090] The wear-resistant particles (chromium carbide particles) and lubricating particles (graphite particles) are sequentially cleaned, soaked, ultrasonicated and dried, and then chromium carbide particles (with a medium particle size of 3 to 5 μm), graphite particles (with a medium particle size of 3 to 5 μm) and a surfactant solution (with a concentration of 2.5 g / L, and the type of surfactant is sodium dodecyl sulfate) are mixed to obtain a mixed solution; the mixed solution, cobalt sulfate, cobalt chloride, sodium hypophosphite and boric acid are mixed to obtain the cobalt-based amorphous composite plating solution (with a pH of 4.5, and the concentrations of the components are: 200 g / L cobalt sulfate, 35 g / L cobalt chloride, 35 g / L sodium hypophosphite, 35 g / L boric acid, 2.5 g / L surfactant, 60 g / L chromium carbide particles, and 30 g / L graphite particles);
[0091] The activated workpiece to be plated and the pure cobalt plate with a clean surface are placed in the cobalt-based amorphous composite plating solution, and the activated workpiece to be plated and the center of the cobalt plate are placed parallel to each other, and the activated workpiece to be plated is used as the cathode, and the pure cobalt plate is used as the anode to connect to an external constant current power supply for electroplating (the electroplating is carried out under stirring conditions, the stirring speed is 325 rpm, the working temperature is 55° C., and the current density is 3A / dm 2 , time is 60min), and then it is thoroughly washed with deionized water and blown dry to obtain a cobalt-based amorphous composite coating.
[0092] Example 2
[0093] The workpiece (made of 30CrMnSiA high-strength steel) was placed in a degreasing liquid (40 g / L sodium phosphate, 30 g / L sodium silicate, 70 g / L sodium hydroxide and 40 g / L sodium carbonate) for degreasing at 70°C for 15 min, and then washed with deionized water for 3 to 5 times to obtain a degreasing workpiece;
[0094] The degreased workpiece is placed in an activation solution (including 250 g / L hydrochloric acid) for activation for 3 minutes, and then washed with deionized water for 2 to 3 times to obtain an activated workpiece to be plated;
[0095] The wear-resistant particles (silicon carbide particles) and the lubricating particles (graphite fluoride particles) are sequentially cleaned, soaked, ultrasonicated and dried, and then silicon carbide particles (medium particle size of 3 to 5 μm), graphite fluoride particles (medium particle size of 3 to 5 μm) and a surfactant solution (concentration of 3 g / L, the types of surfactants are polyethylene glycol (1.5 g / L) and sodium dodecyl sulfate (1.5 g / L)) are mixed to obtain a mixed solution; the mixed solution, cobalt sulfate, cobalt chloride, sodium hypophosphite and boric acid are mixed to obtain the cobalt-based amorphous composite plating solution (pH of 4.5, concentrations of the components are: 200 g / L cobalt sulfate, 35 g / L cobalt chloride, 35 g / L sodium hypophosphite, 35 g / L boric acid, 3 g / L surfactant, 50 g / L silicon carbide particles, 30 g / L graphite fluoride particles);
[0096] The activated workpiece to be plated and the pure cobalt plate with a clean surface are placed in the cobalt-based amorphous composite plating solution, and the activated workpiece to be plated and the center of the cobalt plate are placed parallel to each other, and the activated workpiece to be plated is used as the cathode, and the pure cobalt plate is used as the anode to connect to an external constant current power supply for electroplating (the electroplating is carried out under stirring conditions, the stirring speed is 325 rpm, the working temperature is 55° C., and the current density is 3A / dm 2 , time is 60min), and then it is thoroughly washed with deionized water and blown dry to obtain a cobalt-based amorphous composite coating.
[0097] Example 3
[0098] The workpiece (made of 30CrMnSiA high-strength steel) was placed in a degreasing liquid (40 g / L sodium phosphate, 30 g / L sodium silicate, 70 g / L sodium hydroxide and 40 g / L sodium carbonate) for degreasing at 70°C for 15 min, and then washed with deionized water for 3 to 5 times to obtain a degreasing workpiece;
[0099] The degreased workpiece is placed in an activation solution (including a 250 g / L hydrochloric acid solution) for activation for 3 minutes, and then washed with deionized water for 2 to 3 times to obtain an activated workpiece to be plated;
[0100] The wear-resistant particles (cBN particles) and the lubricating particles (hBN particles) are sequentially cleaned, soaked, ultrasonicated and dried, and then cBN particles (with a median particle size of 3 to 5 μm), hBN particles (with a median particle size of 3 to 5 μm) and a surfactant solution (with a concentration of 3 g / L, and the type of surfactant is sodium dodecyl sulfate) are mixed to obtain a mixed solution; the mixed solution, cobalt sulfate, cobalt chloride, sodium hypophosphite and boric acid are mixed to obtain the cobalt-based amorphous composite plating solution (with a pH of 4.5, and the concentrations of the components are: 200 g / L cobalt sulfate, 35 g / L cobalt chloride, 35 g / L sodium hypophosphite, 35 g / L boric acid, 3 g / L surfactant, 45 g / L hBN particles, and 45 g / L cBN particles);
[0101] The activated workpiece to be plated and the pure cobalt plate with a clean surface are placed in the cobalt-based amorphous composite plating solution, and the activated workpiece to be plated and the center of the cobalt plate are placed parallel to each other, and the activated workpiece to be plated is used as the cathode, and the pure cobalt plate is used as the anode to connect to an external constant current power supply for electroplating (the electroplating is carried out under stirring conditions, the stirring speed is 325 rpm, the working temperature is 55° C., and the current density is 3A / dm 2 , time is 60min), and then it is thoroughly washed with deionized water and blown dry to obtain a cobalt-based amorphous composite coating.
[0102] Comparative Example 1
[0103] The workpiece (made of 30CrMnSiA high-strength steel) was placed in a degreasing liquid (40 g / L sodium phosphate, 30 g / L sodium silicate, 70 g / L sodium hydroxide and 40 g / L sodium carbonate) for degreasing at 70°C for 15 min, and then washed with deionized water for 3 to 5 times to obtain a degreasing workpiece;
[0104] The degreased workpiece is placed in an activation solution (including a 250 g / L hydrochloric acid solution) for activation for 3 minutes, and then washed with deionized water for 2 to 3 times to obtain an activated workpiece to be plated;
[0105] Providing an electroplating solution (pH 4.5, concentrations of components: 200 g / L cobalt sulfate, 35 g / L cobalt chloride, 35 g / L sodium hypophosphite, 35 g / L boric acid and 3 g / L surfactant (specifically sodium dodecyl sulfate);
[0106] The activated workpiece to be plated and the pure cobalt plate with a clean surface are placed in the electroplating solution, and the activated workpiece to be plated and the center of the cobalt plate are placed parallel to each other, and the activated workpiece to be plated is used as the cathode, and the pure cobalt plate is used as the anode to connect to an external constant current power supply for electroplating (the electroplating is carried out under stirring conditions, the stirring speed is 325 rpm, the working temperature is 55 ° C, and the current density is 3A / dm 2, time is 60min), and then thoroughly rinsed and dried with deionized water to obtain a cobalt-based amorphous alloy plating solution.
[0107] Comparative Example 2
[0108] The workpiece (made of 30CrMnSiA high-strength steel) was placed in a degreasing liquid (40 g / L sodium phosphate, 30 g / L sodium silicate, 70 g / L sodium hydroxide and 40 g / L sodium carbonate) for degreasing at 70°C for 15 min, and then washed with deionized water for 3 to 5 times to obtain a degreasing workpiece;
[0109] The degreased workpiece is placed in an activation solution (comprising 250 g / L hydrochloric acid and solution) for activation for 3 minutes, and then washed with deionized water for 2 to 3 times to obtain an activated workpiece to be plated;
[0110] Providing a plating solution (pH 4.5, concentrations of components: 200 g / L cobalt sulfate, 35 g / L cobalt chloride, 35 g / L sodium hypophosphite, 35 g / L boric acid, 3 g / L surfactant (specifically sodium dodecyl sulfate) and 60 g / L cBN particles);
[0111] The activated workpiece to be plated and the pure cobalt plate with a clean surface are placed in the electroplating solution, and the activated workpiece to be plated and the center of the cobalt plate are placed parallel to each other, and the activated workpiece to be plated is used as the cathode, and the pure cobalt plate is used as the anode to connect to an external constant current power supply for electroplating (the electroplating is carried out under stirring conditions, the stirring speed is 325 rpm, the working temperature is 55 ° C, and the current density is 3A / dm 2 , time is 60min), and then it is thoroughly washed with deionized water and blown dry to obtain a cobalt-based amorphous-cBN composite coating.
[0112] Comparative Example 3
[0113] The workpiece (made of 30CrMnSiA high-strength steel) was placed in a degreasing liquid (40 g / L sodium phosphate, 30 g / L sodium silicate, 70 g / L sodium hydroxide and 40 g / L sodium carbonate) for degreasing at 70°C for 15 min, and then washed with deionized water for 3 to 5 times to obtain a degreasing workpiece;
[0114] The degreased workpiece is placed in an activation solution (including a 250 g / L hydrochloric acid solution) for activation for 3 minutes, and then washed with deionized water for 2 to 3 times to obtain an activated workpiece to be plated;
[0115] Providing an electroplating solution (pH 4.5, concentrations of components: 200 g / L cobalt sulfate, 35 g / L cobalt chloride, 35 g / L sodium hypophosphite, 35 g / L boric acid, 3 g / L surfactant (specifically sodium dodecyl sulfate) and 60 g / L hBN particles);
[0116] The activated workpiece to be plated and the pure cobalt plate with a clean surface are placed in the electroplating solution, and the activated workpiece to be plated and the center of the cobalt plate are placed parallel to each other, and the activated workpiece to be plated is used as the cathode, and the pure cobalt plate is used as the anode to connect to an external constant current power supply for electroplating (the electroplating is carried out under stirring conditions, the stirring speed is 325 rpm, the working temperature is 55 ° C, and the current density is 3A / dm 2 , time is 60min), and then it is thoroughly washed with deionized water and blown dry to obtain a cobalt-based amorphous-hBN composite coating.
[0117] Test Case
[0118] Figure 1 The XRD graph (a) and the potentiodynamic polarization curve (b) of the cobalt-based amorphous composite coating (cobalt-based amorphous-chromium carbide / graphite composite coating) described in Example 1 and the cobalt-based amorphous alloy coating described in Comparative Example 1 in a sodium chloride solution with a mass concentration of 3.5% are shown in FIG. Figure 1 From a in Example 1, it can be seen that the cobalt-based amorphous composite coating (cobalt-based amorphous-chromium carbide / graphite composite coating) and the cobalt-based amorphous alloy coating described in Comparative Example 1 both have obvious amorphous diffraction peaks; the cobalt-based amorphous composite coating (cobalt-based amorphous-chromium carbide / graphite composite coating) described in Example 1 obviously has particles entering; Figure 1 As can be seen from b in Example 1, the corrosion resistance of the cobalt-based amorphous composite coating (cobalt-based amorphous-chromium carbide / graphite composite coating) and the cobalt-based amorphous alloy coating described in Comparative Example 1 are both very excellent, and the corrosion current density reaches μA / cm 2 class;
[0119] Figure 2 The microscopic morphology of the cobalt-based amorphous composite coating described in Example 2 at different magnifications is shown in FIG. Figure 2 It can be seen that the cobalt-based amorphous composite coating described in Example 2 is dense and has a complete structure, and the particle distribution is very uniform;
[0120] Figure 3 The wear resistance of the cobalt-based amorphous composite coating described in Example 3 is evaluated, wherein a is the micromorphology and microhardness diagram of the cobalt-based amorphous-cBN / hBN composite coating, and b is the friction coefficient curve of the cobalt-based amorphous-cBN / hBN composite coating; Figure 3 It can be seen that the hardness of the cobalt-based amorphous composite coating described in Example 3 can reach 1435.54 HV, and in the friction and wear test, the friction coefficient is stable and has little fluctuation;
[0121] Table 1 is a performance comparison of the cobalt-based amorphous composite coating described in Example 3, the cobalt-based amorphous alloy plating solution described in Comparative Example 1, the cobalt-based amorphous-cBN composite coating described in Comparative Example 2, and the cobalt-based amorphous-hBN composite coating described in Comparative Example 3. It can be seen from Table 1 that the introduction of wear-resistant particles and lubricating particles into the cobalt-based amorphous composite coating can significantly improve the wear resistance of the coating without reducing the corrosion resistance of the coating, thereby achieving a synergistic improvement in the wear resistance and corrosion resistance of the coating.
[0122] Table 1 Performance comparison of the cobalt-based amorphous composite coating of Example 3, the cobalt-based amorphous alloy plating solution of Comparative Example 1, the cobalt-based amorphous-cBN composite coating of Comparative Example 2, and the cobalt-based amorphous-hBN composite coating of Comparative Example 3
[0123]
[0124]
[0125] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be regarded as the protection scope of the present invention.
Claims
1. A cobalt-based amorphous composite plating solution, characterized in that: The invention comprises the following components: 100-300 g / L of cobalt sulfate, 20-50 g / L of cobalt chloride, 20-50 g / L of sodium hypophosphite, 20-50 g / L of boric acid, 1-5 g / L of surfactant, 0.1-100 g / L of wear-resistant particles and 0.1-100 g / L of lubricating particles.
2. The cobalt-based amorphous composite plating solution according to claim 1, characterized in that: The wear-resistant particles include one or more of chromium carbide particles, cubic boron nitride particles, silicon carbide particles, tungsten carbide particles, aluminum oxide particles, titanium carbide particles, zirconium oxide particles and titanium boride particles.
3. The cobalt-based amorphous composite plating solution according to claim 1, characterized in that: The lubricating particles include one or more of hexagonal boron nitride particles, graphite fluoride particles, molybdenum disulfide particles, graphite particles, polytetrafluoroethylene particles, aluminum nitride particles and boric acid particles.
4. The method for preparing the cobalt-based amorphous composite plating solution according to any one of claims 1 to 3, characterized in that: The following steps are involved: Mixing the wear-resistant particles, the lubricating particles and the surfactant solution to obtain a mixed solution; The mixed solution, cobalt sulfate, cobalt chloride, sodium hypophosphite and boric acid are mixed to obtain the cobalt-based amorphous composite plating solution.
5. A method for preparing a cobalt-based amorphous composite coating, characterized in that: The following steps are involved: Activating the workpiece to be plated in an activation solution to obtain an activated workpiece to be plated; Using the activated workpiece to be plated as a cathode and a pure cobalt plate as an anode, electroplating is performed in a cobalt-based amorphous composite plating solution to obtain the cobalt-based amorphous composite coating; The cobalt-based amorphous composite plating solution is the cobalt-based amorphous composite plating solution according to any one of claims 1 to 3 or the cobalt-based amorphous composite plating solution prepared by the preparation method according to claim 4.
6. The preparation method according to claim 5, characterized in that: Before the activation, the workpiece to be plated is degreased; The degreasing liquid used in the degreasing comprises the following components: 30-50 g / L of sodium phosphate, 10-30 g / L of sodium silicate, 60-80 g / L of sodium hydroxide and 30-50 g / L of sodium carbonate; The degreasing process is carried out at a temperature of 70 to 80° C. and for a time of 10 to 15 minutes.
7. The preparation method according to claim 5, characterized in that: The activation solution includes hydrochloric acid with a concentration of 50 to 250 g / L; The activation time is 2 to 4 minutes.
8. The preparation method according to claim 5, characterized in that: The electroplating is carried out under stirring conditions, and the stirring speed is 200-400 rpm; The working temperature of the electroplating is 50-60°C, and the current density is 2-4A / dm 2 , time is 30 to 120 minutes; the distance between the anode and the cathode is 2 to 5 cm.
9. The cobalt-based amorphous composite coating prepared by the preparation method according to any one of claims 5 to 8.
10. Use of the cobalt-based amorphous composite coating according to claim 9 in wear-resistant and corrosion-resistant parts in aviation, aerospace or high-end mechanical equipment.